Analysis of Constraints in Bumdes Financial Management and the Urgency of Digitizing Financial Reporting at Bumdes in the Mandalika Special Economic Zone (Kek) - Eka Agustiani (Experimental Student Experiences, 2022)
BUMDes or Village Owned Enterprises are drivers of the village economy which not only focus on profit making but also community empowerment and welfare. The West Nusa Tenggara region, especially the Mandalika Special Economic Zone, shows that BUMDes experience problems progressing or running optimally and many have even stopped operating. The question is, what are the obstacles faced by BUMDes, especially related to financial management and what are the benefits and urgency of digitalization for BUMDes managers? This study uses a qualitative approach. The results of the study show that the common obstacles faced by BUMDes are related to the reporting or recording system which is still manual and too many variations of the application provided. in this case, BUMDes managers also provide solutions or suggestions for managing and running BUMDes optimally